Does adding pictures to glosses enhance vocabulary uptake from reading?. (June 2017) - Boers, Frank; Warren, Paul; He, Lin; Deconinck, Julie
Abstract: This article reports three trials of a pen-and-paper experiment where adult L2 learners' recollection of glossed words was tested after they had read a text with or without pictures included in the glosses. Unlike previous studies in which a superiority of multimodal glosses over text-only glosses was claimed, the experiment furnished no evidence that the addition of pictures helped the learners to retain the glossed words any better than providing glosses containing only verbal explanations. When learners were prompted to recall of the written form of the words, the gloss condition with pictures in fact led to the poorest performance. The results suggest that the provision of pictures alongside textual information to elucidate the meaning of novel words may reduce the amount of attention that L2 readers give to the words proper.